From salvation to Alya: the Bulgarian Jews and Bulgarian-Israeli relations (1948–1990). Issue 2 (3rd April 2017) - Marinova-Christidi, Rumyana
Abstract: The basic aim of the present paper is to provide a historical overview of Bulgarian–Israeli relations from 1948 to 1990 (when diplomatic relations were re-established following their break off in 1967), and of Bulgarian state policy towards Jews in the country during the Second World War and the post-war Socialist period. The paper analyses the variety of factors that have affected that 'triangular relationship', such as the positive historical legacy of Bulgarian–Jewish relations that contributed to the salvation of Bulgarian Jews during the Holocaust, and the role and place of Bulgaria and Israel in the cold war confrontation that dominated international politics from the end of the 1940s to 1989.